"It's On Us." The Role of Social Media and Rape Culture in Individual Willingness to Mobilize Against Sexual Assault. Issue 1 (2nd January 2017) - Armstrong, Cory L.; Mahone, Jessica
Abstract : Stopping sexual violence has become a key issue in the public and media agenda. This study examines the role of social media and bystander intervention in predicting an individual's willingness to engage in collective action against sexual violence. Two surveys were conducted in fall 2014 and early 2015 examining young adults' views of social networking sites, rape culture, and collective action. Results indicated that gender and bystander intervention were key predictors of willingness to engage in collective action, along with the privacy concerns of social network users. Views supporting rape culture were found to have a negative association. Implications are discussed.